MiR319a‐targeted PtoTCP20 regulates secondary growth via interactions with PtoWOX4 and PtoWND6 in Populus tomentosa. Issue 4 (31st July 2020) - Hou, Jie; Xu, Huimin; Fan, Di; Ran, Lingyu; Li, Jianqiu; Wu, Shuang; Luo, Keming; He, Xin‐Qiang
Summary: Secondary growth is a key characteristic of trees, which requires the coordination of multiple regulatory mechanisms including transcriptional regulators and microRNAs (miRNAs). However, the roles of microRNAs in the regulation of secondary growth need to be explored in depth. Here, the role of miR319a and its target, PtoTCP20, in the secondary growth of Populus tomentosa stem was investigated using genetic and molecular analyses. The expression level of miR319a gradually decreased from primary to secondary growth in P. tomentosa, while that of PtoTCP20 gradually increased. MiR319a overexpression in seedlings resulted in delayed secondary growth and decreased xylem production, while miR319a knockdown and PtoTCP20 overexpression promoted secondary growth and increased xylem production. Further analysis showed that PtoTCP20 interacted with PtoWOX4a and activated PtoWND6 transcription in vitro and in vivo . Our data show that PtoTCP20 controls vascular cambium proliferation by binding to PtoWOX4a, and promotes secondary xylem differentiation by activating PtoWND6 transcription, thereby regulating secondary growth in P. tomentosa . Our findings provide insight into the molecular mechanisms underlying secondary growth in trees.